Factors affecting the structure of lyotropic liquid crystals and the correlation between structure and drug diffusion. Issue 13 (13th February 2018) - Huang, Yiming; Gui, Shuangying
Abstract : Factors such as amphiphilic molecules, water content, temperature, pressure, light and magnetic field on the structures of LLCs. Abstract : Lyotropic liquid crystals (LLCs) formed by the self-assembly of amphiphilic molecules in a solvent (usually water) have attracted increasingly greater attention in the last few decades, especially the lamellar phase (Lα ), the reversed bicontinuous cubic phase (Q2 ) and the reversed hexagonal phase (H2 ). Such phases offer promising prospects for encapsulation of a wide range of target molecules with various sizes and polarities owing to the unique internal structures. Also, different structures of mesophases can give rise to different diffusion coefficients. The bicontinuous cubic phase and the hexagonal phase have been demonstrated to control and sustain the release of active molecules. Furthermore, the structures are susceptible to many factors such as water content, temperature, pH, the presence of additives etc. Many researchers have been studying these influencing factors in order to accurately fabricate the desired phase. In this paper, we give a review of the characteristics of different structures of liquid crystalline phases, the influencing factors on the phase transition of liquid crystals and the relationship between structures of LLC and drug diffusion. We hope our review will provide some insights into how to manipulate in a controlled manner the rate of incorporating and transferring molecules by altering the structure of lyotropic mesophases.